VD_FINDINFO HC / 2010 / 81 vom 8. Dezember 2009 - VD Tribunal cantonal (2009)
LIBÉRATION CONDITIONNELLE, RÉVOCATIONEN GÉNÉRAL, CONSOMMATION DE STUPÉFIANTS, PROPORTIONNALITÉ | 95 al. 5 CP, 95 CP, 485m CPP, 26 LEP, 38 al. 1 LEP, 54 CPM